Previous Cardiac Surgery: a Predictor of Mortality in Aortic Valve Replacement? - Dayan,Victor (2019)
Abstract Introduction: Previous cardiac surgery (PCS) is a risk factor for operative mortality in pa-tients undergoing reoperative aortic valve replacement (AVR) and may be influenced by the volume of patients in each center. The aim of this study was to evaluate the results of AVR in patients with previous cardiac surgery in a low volume cardiac center (400 cases per year). Methods: Between January 2006 and December 2016, 854 patients underwent isolated AVR surgery at our institution. Of these, 70 had PCS. Propensity match (PM) was per-formed to balance basal covariates. Operative mortality and survival were the primary outcomes. Results: The PCS and first-time surgery (FTS) groups had significant differences in base-line characteristics (PCS group were older, higher incidence of hypertension, endocarditis, NYHA III/IV, lower LVEF, higher creatinine and higher EuroSCORE). In the unmatched population, patients with PCS had higher operative mortality (17.1% vs. 4.6%, P=0.001). In the PM groups, this difference was not significant (12.5% and 3.6%, P=0.08). The only independent predictors for operative mortality found in the PCS group were age and fe-male gender. Age and diabetes were identified as the only independent predictors of sur-vival. Conclusion: PCS was not a predictor for operative mortality nor long-term survival in pa-tients undergoing isolated aortic valve replacement.